Locating and Preserving the Sphenopalatine Ganglion in Endoscopic Endonasal Pterygopalatine Fossa Surgery: An Anatomical Study. Issue 3 (May 2020) - Spielman, Daniel B.; Kim, Matthew; Overdevest, Jonathan; Gudis, David A.
Background: The pterygopalatine fossa (PPF) contains numerous important neurovascular structures; notably, the sphenopalatine ganglion (SPG), the maxillary branch of the trigeminal nerve (V2), and the internal maxillary artery. With the advent of extended endoscopic endonasal surgery, the surgical anatomy of the PPF warrants increased investigation. Intraoperative dissection and preservation of the SPG is essential to prevent postoperative xeropthalmia and facial hypoesthesia. Objective: This study aims to (1) describe a novel dissection technique for identifying the SPG and (2) define the SPG location relative to the sphenopalatine foramen (SPF), which is a consistently identifiable landmark. Methods: Eight cadaveric PPFs were dissected in step-wise fashion. An endoscopic medial maxillectomy was performed, the SPF was identified, and the posterior maxillary wall was resected. The maxillary branch of the trigeminal nerve (V2) was identified anterolaterally in its infraorbital canal and traced medially to identify the pterygopalatine nerve to the SPG. The lateral distance and superior/inferior distance from the SPG to the fixed SPF was measured. Results: The surgical technique described allowed for reliable identification of the SPG. The SPG was located on average 4.5 ± 1.1 mm lateral and 1 ± 1.4 mm inferior to the SPF. Conclusion: Identification and preservation of the SPG is necessary to prevent complications in endoscopic endonasal PPF surgery. The SPG can be reliably located near the SPF by following the pterygopalatine nerve branch of V2.